Significance of patient-reported outcomes for occupational resumption and quality of life after cardiac rehabilitation. (25th November 2020) - Salzwedel, A; Koran, I; Langheim, E; Schlitt, A; Nothroff, J; Bongarth, C; Wrenger, M; Wegscheider, K; Voller, H
Abstract: Introduction: Comprehensive cardiac rehabilitation (CR) programs based on the bio-psycho-social approach of the international classification of functioning and disease are carried out to achieve improved prognosis, superior health-related quality of life (HRQL) and social integration. We aimed to identify predictors of returning to work (RTW) and HRQL among cardiovascular risk factors and physical performance as well as patient-reported outcome measures (PROMs) modifiable during CR. Methods: We designed a prospective observational multi-center study and enrolled 1, 586 patients (2017/18) in 12 German rehabilitation centers regardless of their primary allocation diagnoses (e.g. acute myocardial infarction (AMI), coronary artery bypass grafting (CABG), coronary artery disease (CAD), valvular disease). Besides general data (e.g. age, gender, diagnoses), parameters of risk factor management (e.g. smoking, lipid profile, hypertension, lifestyle change motivation), physical performance (e.g. maximum exercise capacity, endurance training load, 6-min walking distance), and PROMs (e.g. depression, heart-focused anxiety, HRQL, subjective well-being, somatic and mental health, pain, general self-efficacy, pension desire as well as self-assessment of occupational prognosis using several questionnaires) were documented at CR admission and discharge. 6 months after discharge, status of RTW and HRQL (SF-12) were captured by a follow-up (FU) survey and analyzed in multivariable regression models with multiple imputation of missing values. Results: Out of the study participants, 1, 262 patients (54±7 years, 77% men) responded to the follow-up survey and could be analyzed regarding the outcome parameters. Most of them were assigned to CR primarily due to AMI (40%) or CAD without myocardial infarction (18%), followed by heart valve diseases in 12% of patients and CABG (8%). 864 patients (69%) returned to work within the follow-up period. Pension desire, negative self-assessed occupational prognosis, heart-focussed anxiety, major life events, smoking and heart failure were negatively associated with RTW, while higher endurance training load, HRQL and work stress were positively associated (Figure 1). HRQL after 6 months was determined more by PROMs (e.g. pension desire, heart-focused anxiety, physical/mental HRQL in SF-12, physical/mental health in indicators of rehab-status questionnaire (IRES-24), stress, well-being in the World Health Organization well-being index and self-efficacy expectations) than by clinical parameters or physical performance. Conclusions: Patient-reported outcome measures predominantly influenced RTW and HRQL in heart-disease patients, whereas patients' pension desire and heart-focussed anxiety had a dominant impact on all investigated endpoints. Therefore, the multi-component CR approach focussing on psychosocial support is crucial for subjective health prognosis and occupational resumption. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): German pension insurance